The Prevalence of Antibiotics Drug Resistant in Surgery Unit of Banglamung Hospital, 2015 - โสตถิวรรณ์ ธิปัตย์; สังฆพรหม จักรวาล; พรหมรัตน์ ปริวรรต; ผาสุข อโณทัย (Progress in Applied Science and Technology, 2017)
Nosocomial infection is an important problem that occurs with patients who were admitted in the hospital. It can be found in all levels of hospitals. The prevalence varies from place to place and the numbers of cases increase every year. This infection leads to increased severity of the disease and prolong of hospitalization. The most common sites that nosocomial infection can be found are urinary tract, surgical site, respiratory tract and bloodstream. Objective: The study aimed to determine the prevalence of resistant bacteria found in the male surgery ward, Banglamung Hospital and compared the costs of maintaining the period of bacteria resistant. The number of 28 samples was found resistant bacteria from October 2014 to September 2015 and analysis by using percentage, chisquare crosstab. The results showed that there were 28 patients who were resistant bacteria 37 times (9.61%) average age of 48.46 years. Total cost of treatment 1,496,878 baht, the highest was 49,923 Baht. Total day bed 782 days (2 years, 1 month, 22 days). Most commonly obtained from wound-pus / discharge 83.78% (31 times), E.coli were the most commonly 51.35% (19 times) the prevalence of resistant bacteria 4.93 % and Staph aureus (MRSA) 5.40% (2 times) accounted for 0.52% of prevalence in unit. The resistant bacteria 53.57% after stay in hospital more 7 days and found 39.28% in less 3 day group. The susceptibility showed that Imipenem 78.38% and resistant to Ceftazidime 67.57%. The correlation found the group of patient who stayed in more 7 days were significant statistical level at .05 in more 10,001 baht of treatment = 13.997, = 6, = .03), with length of stay> 22 days = 10.175, = 4, = .038) . In specimen collection less than 3 days = 12.907, = 4, = .012) had highly correlation more 7 day group which length of stay and cost of treatment significant at .05 = 9.972, = 4, = .041) . The results were found to be useful in the planning of resistance management solutions. And guidance systems for use of antimicrobial surgical patients. Banglamung Hospital And uses a database to monitor the system in the neighborhood - Transfer between hospitals in neighboring areas.